Drosophila as a Model Organism in Host–Pathogen Interaction Studies - Younes, Salma; Al-Sulaiti, Asma; Nasser, Elham Abdulwahab Ahmed; Najjar, Hoda; Kamareddine, Layla (Frontiers in Cellular and Infection Microbiology, 2020)
Owing to the genetic similarities and conserved pathways between a fruit fly and mammals, the use of the Drosophila model as a platform to unveil novel mechanisms of infection and disease progression has been justified and widely instigated. Gaining proper insight into host–pathogen interactions and identifying chief factors involved in host defense and pathogen virulence in Drosophila serves as a foundation to establish novel strategies for infectious disease prevention and control in higher organisms, including humans.